2012
DOI: 10.1080/15459624.2012.693836
|View full text |Cite
|
Sign up to set email alerts
|

Exposure too-Toluidine, Aniline, and Nitrobenzene in a Rubber Chemical Manufacturing Plant: A Retrospective Exposure Assessment Update

Abstract: The National Institute for Occupational Safety and Health previously conducted a retrospective cancer incidence and mortality study of workers employed at a rubber chemical manufacturing plant. Compared with New York State incidence, the bladder cancer risk was 6.5 times higher for workers considered to have definite exposure to ortho-toluidine and aniline, and 4 times higher for workers with possible exposure. Exposure characterization in the original study utilized a surrogate measure based only on departmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(45 citation statements)
references
References 15 publications
1
42
0
2
Order By: Relevance
“…In 1990, NIOSH measured breathing zone air levels of o -toluidine (and aniline and nitrobenzene) in different processes throughout the Rubber Chemicals department; individual personal breathing zone o -toluidine concentrations ranged from 0.02 to 0.37 ppm, and geometric means ranged from 0.051 to 0.096 ppm. These measurements concur with those provided by the company for 1976–2004, and show a decrease in exposure concentrations over time 6. They also confirmed that exposure levels of o -toluidine were generally higher than those of aniline and nitrobenzene.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…In 1990, NIOSH measured breathing zone air levels of o -toluidine (and aniline and nitrobenzene) in different processes throughout the Rubber Chemicals department; individual personal breathing zone o -toluidine concentrations ranged from 0.02 to 0.37 ppm, and geometric means ranged from 0.051 to 0.096 ppm. These measurements concur with those provided by the company for 1976–2004, and show a decrease in exposure concentrations over time 6. They also confirmed that exposure levels of o -toluidine were generally higher than those of aniline and nitrobenzene.…”
Section: Discussionsupporting
confidence: 88%
“…Likewise, increased bladder cancer incidence was observed even at the lower cumulative rank level. Air monitoring data showed that exposure concentrations even among the highest exposed workers were very low relative to existing occupational exposure limits 6. Currently, the Occupational Safety and Health Administration Permissible Exposure Limit (PEL) for o -toluidine is 5 ppm as an 8-h time-weighted average.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations